Initial Design of Dual Axis Solar Tracking System with the Addition of Camera and Cooling System - Hafidz Zharif; Dian Budhi Santoso; Reni RahmaDewi (Politeknik Negeri Jakarta, 2023)
Solar panels have been widely used to determine solar energy as an electrical energy generator. However, the installation of solar panels is still static, so it cannot follow the sun's movement optimally. Solar panels with dual-axis tracking have a wide range in the tracking process. The range that can be tracked by dual-axis tracking is azimuth angle and altitude, while single-axis tracking can only choose one side of the angle. In this study, the initial design of the dual-axis solar tracking system was made with cameras and cooling systems combined with heatsinks and tubular pipes. The design made is in the form of a CAD design using SolidWorks software, and the design made will be used for subsequent research, In this solar panel, the fill factor results are 0.634, and the efficiency of solar panels is 17.53% with the addition of a cooling system which can reduce the temperature of solar panels is expected to be higher efficiency. The study results were obtained in the design of a solar tracker with the addition of a cooling system that will later reduce the temperature and increase the efficiency of solar panel about 0.38% every 1℃ decreases of temperature.